Biomass direct gasification for electricity generation and natural gas replacement in the lime kilns of the pulp and paper industry: A techno-economic analysis. (15th December 2021) - Rey, J.R.C.; Pio, D.T.; Tarelho, L.A.C.
Abstract: This study shows a comparative techno-economic analysis of the integration of biomass gasification for generation of producer gas to be used in electricity production and to replace natural gas in the lime kilns of the pulp and paper industry. Three study cases with alternative configurations of the energy system integrating biomass gasification were analysed, including or not the co-generation of electricity and thermal energy, namely: i) Case I, for generation of electricity from residual forest biomass (RFB) in an integrated gasification combined cycle system, ii) Case II, generation of producer gas by RFB gasification for replacement of natural gas in the burners of a lime kiln, and iii) Case III, as an integration of Cases I and II for combined production of electricity and heat. Residual forest biomass from eucalyptus logging activities for feedstock processing for the pulp and paper industry was considered as fuel for direct (air) gasification in bubbling fluidized bed. The analysis made is supported on review reports, namely, the evaluation of the existing literature on investment projects in biomass power plants, and on experimental investigation for determining the composition of the producer gas from gasification of the selected feedstock. An economic model was developed that combines the net present value, internal rate of return and payback period. The main results of the energy system analysis show that the net electricity generation is between 72 and 83 GWh/year, while the production of CaO in the lime kiln supported by combustion of producer gas, is 82.12 kt/year, and a global energy efficiency between 21.70 and 34.17 % is achieved for the analysed configurations of the energy system. The results of the economic analysis show a positive NPV, an IRR greater than the discount rate and a PBP less than the useful life of the plant. The sensitivity analysis shows quite favorable investment projections given the low probability that the NPV will reach negative values and compromise the economic viability of the project. Highlights: The technical-economic viability of the forest biomass residues gasification is addressed. Integration of IGCC concepts in the pulp and paper industry is reviewed. The opportunities and drawbacks of IGCC in the pulp and paper industry are discussed. Replacement of natural gas for producer gas for electricity generation and lime production is analysed. A Monte Carlo sensitivity analysis is performed.